Integrating online and offline business of a retailer: A customer utility based inventory model. (January 2023) - Panja, Subrata; Mondal, Shyamal Kumar
Abstract: Looking at the digital transformation in the retail industry many bricks and mortar (B&M) retailers are interested to run their business in an integrated way. In that direction, our study analyses a joint online and offline retail business of a retailer. Here, a utility based approach has been proposed to reflect the customers' choice behaviour over the available alternatives, where we have incorporated product availability factor along with product valuation, price and hassle cost, as the observed factors. Moreover, keeping in mind the unobserved factors we have proposed the logit model structure for the demand estimation of the two channels. Categorizing the product based on the valuation, our findings reveal that for products like electronic and home appliances, the retailer should give more priority to low-valued and moderately premium items for his/her joint online and offline business, whereas for items like books and games, such business strategy would be the preferred choice irrespective of product premiumness. Examining the customers' price sensitivities towards the two shopping platforms, we find that when the online price sensitivity is lower than offline, customers are more intended to buy the premium category items online. On the other side, under higher online price sensitivity, initially, for lower valued items customers prefer to buy from B&M store but when the product belongs to the premium category, a balanced shopping behaviour among the customers is noticed. We have also discussed that customers' hassle costs in different platforms have many strategical importance on the joint online and offline business. Highlights: An integrated online and offline business structure has been considered. A utility based approach has been used to reflect the customers' choice behaviour. Logit model structure has been used for demand estimation. Several important insights are presented based on the product categorization. We find that hassle cost during shopping have many strategic importance on the channel preferences.